Our Evolving Understanding of Kawasaki Disease Pathogenesis: Role of the Gut Microbiota - Kaneko, Kazunari; Akagawa, Shohei; Akagawa, Yuko; Kimata, Takahisa; Tsuji, Shoji (Frontiers in Immunology, 2020)
Kawasaki disease (KD) was first described by Dr. Tomisaku Kawasaki in 1967. The etiology of KD has been studied comprehensively but remains largely unknown. The disease seems to result from the interplay of genetic and environmental susceptibility factors with infectious triggers, followed by a subsequent abnormal immune response characterized by increased levels of inflammatory cytokines and chemokines during the acute phase. Evidence has mounted to suggest that an imbalance between T helper 17 cells (Th17s) and regulatory T cells (Tregs) is associated with aberrant immune responses in KD. Recent advances in culture-independent techniques for detection and identification of intestinal commensal bacteria enabled the discovery that Th17 and Treg differentiation are regulated by short chain fatty acids (SCFAs), in particular butyrate, produced by the gut microbiota. This finding provided a mechanistic link between dysbiosis, defined as changes in the composition of the gut microbiota, and various inflammatory diseases. On this basis, we propose that dysbiosis, with reduced production of SCFAs leading to imbalances of Th17s/Tregs, could be involved in the etiology of KD. A pilot study supported this hypothesis, as only fecal concentrations of butyrate were significantly reduced in KD patients among SCFAs. This evolving perspective prompted us to undertake metagenomic analyses of bacterial DNA from the feces of KD patients who were antibiotic-naïve at diagnosis. Simultaneous measurements of Th17s/Tregs in peripheral blood and SCFA concentrations in feces would provide valuable information regarding the association between dysbiosis and dysregulated immune responses in KD.